Evaluation of hearing loss in patients with neonatal unconjugated hyperbilirubinemia - Korkmaz, Baki; Şan, İmran and Kar, Murat and İynen, İsmail (ENT Updates, 2013)
Objective: To investigate how the various bilirubin levels on patients with neonatal unconjugated hyperbilirubinemia affect the hearing loss in early periods. Methods: One hundred twenty one infants (89 with indirect hyperbilirubinemia and 32 healthy subjects) were included in the study. Seven working groups (Group I-VII) were formed in accordance with their bilirubin levels, which were 19.9 mg/dl and below, 20.0-29.9 mg/dl, 30 mg/dl and over, 10.95-38.08 mg/dl and premature, 20.01-38.08 mg/dl and with no exchange transfusion, 24.7-46.65 mg/dl and with exchange transfusion and control group, respectively. Each infant was controlled in terms of hearing tests including tympanogram, stapes reflex, otoacoustic emission at least 3 times within 12 months period. The auditory brainstem responses and free area behavioral threshold tests were performed on the cases which were found to have hearing loss by those tests. Results: Stapes reflex could not be found on 1, 6, 3, 1, 4, 7 infants in the Groups of I-VI, respectively. Cochlear response in otoacoustic emission was not observed on 2, 8, 7, 2, 5, 11 infants, respectively. In the auditory brainstem responses, wave V was not found on 1, 4, 1, 1, 3, 2 infants, respectively. Free area behavioral threshold test performed on 6 patients whose auditory thresholds were thought to be low revealed normal threshold in 5 patients and extremely sensorineural hearing loss in 1 patient. No significant difference was observed among all working groups in terms of hearing loss. Conclusion: In infants exposed to indirect hyperbilirubinemia (>20 mg/dl) for a long time, cochlear and auditory functions could be affected. Hearing loss, which is one of the probable complications of postnatal bilirubin encephalopathy, is required to be followed up closely for early diagnosis.